In splendid isolation: a new cloud forest species expands the distribution of Myrceugenia (Myrtaceae) into Las Yungas and adds a new genus to the flora of Bolivia - Proença, Carolyn Elinore Barnes; Vieira, Fábio Christiano Speck; Sano, Paulo Takeo; Villarroel, Daniel (Phytotaxa, 2024)
Myrceugenia is a temperate or subtropical genus of c. 50 species with a disjunct distribution across South America. The ‘western’ species occur in central Chile and north-western Argentina with one species in the Juan Fernández Islands. The ‘eastern’ species occur in Uruguay, southern Brazil, and marginal regions of Argentina and Paraguay, reaching montane eastern Brazil (two isolated taxa in Central Brazil). It is hypothesized that Myrceugenia once grew across the temperate forests of southern South America, but that oceanic transgressions and the elevation of the Andes during the Miocene divided its populations as the forests retracted from the centre of the continent. The Las Yungas floristic province is a strip of cool, temperate forest that runs along the eastern slopes of the Andes from Venezuela to northern Argentina; Myrceugenia was not known to occur there. We report the discovery of a new species of Myrceugenia in southern Las Yungas (Bosque Tucumano Boliviano). It is distinct from all other species of the genus by the combination of solitary flowers, sub-ancipitate hypanthium, bilocular locules, and 12-13 clustered ovules. The phylogeny of Myrceugenia shows geographic structuring with three basal western clades and one derived eastern clade. The isolated taxa of Myrceugenia from Central Brazil were sisters, respectively, to the rest of the eastern clade and to one of its two subclades, suggesting that isolated taxa are relictual. The discovery of this species has made Myrceugenia the only genus of Myrtaceae to grow in the three cool, humid forests of southern South America.